Evaluation of the stability of open bite treatment using a removable appliance with palatal crib combined with high-pull chincup - Ferreira,Fernando Pedrin Carvalho (2012)
OBJECTIVE: The aim of this prospective study was to cephalometrically analyze the stability of dentoalveolar and skeletal changes produced by a removable appliance with palatal crib associated to high-pull chincup in individuals with anterior open bite treated for 12 months, and compare them to individuals with similar malocclusion and age, not submitted to orthodontic treatment, also followed for the same period. METHODS: Nineteen children with a mean age of 9.78 years old treated for 12 months with a removable appliance with palatal crib associated with chincup therapy were evaluated after 15 months (post-treatment period) and compared with a control group of 19 subjects with mean age of 9.10 years with the same malocclusion that was followed-up for the same period. Seventy-six lateral cephalograms were evaluated at T1 (after correction) and T2 (follow-up) and cephalometric variables were analyzed by statistical tests. RESULTS: The results did not show significant skeletal, soft tissue or maxillary dentoalveolar changes. Overall, treatment effects on the experimental group were maintained at T2 evaluation with an increase of 0.56 mm in overbite. Overjet and maxillary incisors/molars position (vertical and sagittal) remained essentially unchanged during the study period. Only mandibular incisors showed significant changes (labial inclination and protrusion) compared to control group. CONCLUSIONS: Thus, it can be concluded that the early open bite treatment with a removable appliance and palatal crib associated with high-pull chincup therapy provided stability of 95%.